Candida auris: a quick review on identification, current treatments, and challenges - Cernáková, Lucia (2021)
Candida auris is a novel and major fungal pathogen that has triggered several outbreaks in the last decade. The few drugs available to treat fungal diseases, the fact that this yeast has a high rate of multidrug resistance and the occurrence of misleading identifications, and the ability of forming biofilms (naturally more resistant to drugs) has made treatments of C. auris infections highly difficult. This review intends to quickly illustrate the main issues in C. auris identification, available treatments and the associated mechanisms of resistance, and the novel and alternative treatment and drugs (natural and synthetic) that have been recently reported. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.